Interaction between Geogrid Reinforcement and Tire Chip-Sand Mixture - Tawatchai Tanchaisawat; D.T. Bergado; Suriyon Prempramote (Agriculture and Natural Resources, 2006)
The interaction between reinforcing and backfill materials is a significant factor for analysis and design of reinforced earth structures. It can be simplified as pullout resistance and direct shear resistance, which depend on both reinforcing and backfill materials. This study is aimed at studying the interaction between geogrid and tire chip-sand mixture. Numerous experiments including index tests, compaction tests, pullout tests and large-scale direct shear tests were conducted to meet the mentioned objectives. Saint-Gobain and Polyfelt geogrids were selected as reinforcing materials whereas tire chipsand mixtures at the mixing ratios of 30:70, 40:60 and 50:50 % by weight were used as fill materials. The mixture at the mixing ratio of 30:70 % was found to be the most suitable fill material. The pullout resistance and the pullout interaction coefficients of Saint-Gobain geogrids were higher than those of Polyfelt geogrids. In contrast, the direct shear resistance, the direct shear interaction coefficients, and the efficiency values of Polyfelt geogrids were higher than those of Saint-Gobain geogrids. The ultimate tensile strength of Polyfelt geogrid was slightly lower than that of Saint-Gobain geogrid. Finally, Polyfelt geogrid and the tire chip-sand mixture at the mixing ratio of 30:70 % by weight were recommended as reinforcing and backfill materials for field applications.